IFN-γR/STAT1 signaling in recipient hematopoietic antigen-presenting cells suppresses graft-versus-host disease - Caisheng Lu; Huihui Ma; Liangsong Song; Hui Wang; Lily Wang; Shirong Li; Stephen M. Lagana; Antonia R. Sepulveda; Kasper Hoebe; Samuel S. Pan; Yong-Guang Yang; Suzanne Lentzsch; et al. (The Journal of Clinical Investigation, 2023)
The absence of IFN-γ receptor (IFN-γR) or STAT1 signaling in donor cells has been shown to result in reduced induction of acute graft-versus-host disease (GVHD). In this study, we unexpectedly observed increased activation and expansion of donor lymphocytes in both lymphohematopoietic organs and GVHD target tissues of IFN-γR/STAT1–deficient recipient mice, leading to rapid mortality following the induction of GVHD. LPS-matured, BM-derived Ifngr1–/– Stat1–/– DCs (BMDCs) were more potent allogeneic stimulators and expressed increased levels of MHC II and costimulatory molecules. Similar effects were observed in human antigen-presenting cells (APCs) with knockdown of Stat1 by CRISPR/Cas9 and treatment with a JAK1/2 inhibitor. Furthermore, we demonstrated that the absence of IFN-γR/STAT1 signaling in hematopoietic APCs impaired the presentation of exogenous antigens, while promoting the presentation of endogenous antigens. Thus, the indirect presentation of host antigens to donor lymphocytes was defective in IFN-γR/STAT1–deficient, donor-derived APCs in fully donor chimeric mice. The differential effects of IFN-γR/STAT1 signaling on endogenous and exogenous antigen presentation could provide further insight into the roles of the IFN-γ/STAT1 signaling pathway in the pathogenesis of GVHD, organ rejection, and autoimmune diseases.